Os presidencialismos atuais do Brasil e da França: aproximações, diferenças e contribuições possíveis - Miranda, Gabriela Christina Schweitzer de (2023)
2. This dissertation is a scientific investigation about executive branch and presidentialism in Brazil and France, a comparative study pointing out some differences and suggesting possible contributions to Brazilian law. By considering the lessons learnt from the French political system, this study offers valuable insights into how Brazil could improve political stability and government effectiveness through reforms adapted to its specific reality. The differences between presidential and semi-presidential systems were analysed. The research brought the Brazilian constitutional evolution and the importance of exploring innovative and adaptable approaches, based on relevant foreign experiences, when discussing possible reforms in the Brazilian political scenario, contributing to the ongoing discussion about the improvement of the country's democratic institutions and presenting a proposal for an Amendment to the Brazilian Constitution for the adoption of semi-presidentialism.